Design of Internet Controlled Switch Box using IoT - Karthi, A.; Sabaresh, G. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
IoT (Internet of things) is a developing technique that is more useful to control or monitor the appliances via internet. Existing appliances can be connected to WIFI network and to internet with the help of ESP8266 microcontroller.Â Â A web socket is implemented in ESP8266 and it can be accessed through mobile Android application. Home appliances connected in smart switch box, people can control appliances anytime anywhere. This paper gives overview of Internet Controlled Switch Box.